2009
DOI: 10.1017/s0950268809990501
|View full text |Cite
|
Sign up to set email alerts
|

A hypothesis for the 2007 dengue outbreak in Singapore

Abstract: A previous mathematical model explaining dengue in Singapore predicted a reasonable outbreak of about 6500 cases for 2006 and a very mild outbreak with about 2000 cases for 2007. However, only 3051 cases were reported in 2006 while more than 7800 were reported in the first 44 weeks of 2007. We hypothesized that the combination of haze with other local sources of particulate matter had a significant impact on mosquito life expectancy, significantly increasing their mortality rate. To test the hypothesis a mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Our findings with respect to effect of haze on mosquitoes are in general agreement with Massad et al [ 28 ]. They concluded that the fewer than expected number of dengue cases in Singapore in 2006 was caused by an increase in mosquito mortality due to the disproportionate haze affecting the country that year.…”
Section: Resultssupporting
confidence: 93%
“…Our findings with respect to effect of haze on mosquitoes are in general agreement with Massad et al [ 28 ]. They concluded that the fewer than expected number of dengue cases in Singapore in 2006 was caused by an increase in mosquito mortality due to the disproportionate haze affecting the country that year.…”
Section: Resultssupporting
confidence: 93%
“…The above letter by Ooi et al entitled 'The 2007 dengue outbreak in Singapore ' heavily criticizes our paper 'A hypothesis for the 2007 dengue outbreak ' [1]. Ooi et al suggest that our explanation for the mismatch between the observed dengue incidence in Singapore and that predicted by our earlier model is unfounded.…”
Section: R Eferencesmentioning
confidence: 55%
“…To the Editor We read with disappointment the work by Massad and others entitled 'A hypothesis for the 2007 dengue outbreak in Singapore' [1]. The authors blamed the haze that resulted from forest fires in Sumatra in 2006 for the mismatch between the observed dengue incidence in Singapore and that predicted by their model [2].…”
Section: The 2007 Dengue Outbreak In Singaporementioning
confidence: 99%
“…A recent paper proposed haze as a possible additional factor influencing dengue transmission [8]. This hypothesis was based on several observations : smoke, a component of haze, is anecdotally claimed to repel biting insects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Communities in the Solomon Islands use fire to protect themselves from mosquitoes [11]. Based on mathematical modelling on Singapore's year to year oscillations of dengue, Massad et al postulated that the reduction of dengue cases in 2006 was due to an increase in mosquito mortality in response to the disproportionate haze affecting the country that year [8]. The 2006 Southeast Asian haze event was caused by continued uncontrolled burning from 'slash and burn ' cultivation in Indonesia, and affected several countries in the Southeast Asian region including Singapore.…”
Section: Introductionmentioning
confidence: 99%